2020
DOI: 10.1097/md.0000000000018961
|View full text |Cite
|
Sign up to set email alerts
|

Depressed sympathovagal modulation indicates sepsis in patients with suspected infection

Abstract: This study explored whether sympathovagal modulation assessed through frequency domains of heart rate variability (HRV) can indicate sepsis in patients with suspected infection. In total, 370 consecutive adult patients with suspected infection admitted to the emergency department were enrolled in this single-center cohort study. A continuous 10-minute electrocardiography for HRV analysis was recorded immediately for these patients after inclusion. Patients were stratified into non-sepsis and sepsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In a recent retrospective population based cohort study, Hsu W, et al, reported that established RAS blockade therapy before sepsis will be protective for the sepsis related mortality [1]. These results seems to be in line with the recent study showing depressed sympathetic modulation can be a signal for sepsis in patient with infection [2]. Some mediators to suppress sympathetic nervous system may be required for sustained hypotension so that those mediators may not be effective if additional blocking is not possible due to already established sympathetic blockade.…”
Section: General Aspects Of Infection and Hypertension Managementsupporting
confidence: 62%
“…In a recent retrospective population based cohort study, Hsu W, et al, reported that established RAS blockade therapy before sepsis will be protective for the sepsis related mortality [1]. These results seems to be in line with the recent study showing depressed sympathetic modulation can be a signal for sepsis in patient with infection [2]. Some mediators to suppress sympathetic nervous system may be required for sustained hypotension so that those mediators may not be effective if additional blocking is not possible due to already established sympathetic blockade.…”
Section: General Aspects Of Infection and Hypertension Managementsupporting
confidence: 62%
“…This gains support from the observations that CLP rats exhibited (i) diminished overall cardiac autonomic control as indexed by the falls in SDNN and total power, and (ii) shifts in sympathovagal balance towards parasympathetic predominance as verified by the reductions in LF/HF ratios. The increased vagal activity and depressed sympathetic modulation of the heart have been reported in septic patients (Hsu et al, 2020). Clinically, the depressed HRV in septic patients correlates with worsened prognosis and mortality in sepsis (Barnaby et al, 2002;Pontet et al, 2003;de Castilho et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…This potential to modulate the activity of the autonomic nervous system was elegantly shown in patients who underwent pinealectomy—a therapy with exogenic melatonin restored the sympathetic–parasympathetic balance in these subjects [ 75 ]. This ability to harmonize both parts of the autonomic nervous system may be especially important in septic patients, in which the disruption of sympathovagal modulation may even precede the development of a systemic inflammatory response [ 76 ]. It can be speculated that the use of melatonin may be parallel to the stimulation of the vagal nerve, as successfully implemented in animal models of sepsis [ 77 ].…”
Section: Clinical Role Of Melatoninmentioning
confidence: 99%